Phase II Trial of the Combination of Temsirolimus and Sorafenib in Advanced Hepatocellular Carcinoma with Tumor Mutation Profiling - Robin K. Kelley (Liver Cancer, 2021)
Background: The mammalian target of rapamycin (mTOR) pathway is upregulated in nearly half of hepatocellular carcinoma (HCC) tumors and is associated with poor prognosis. In preclinical models of HCC, the combination of mTOR pathway inhibition with the multikinase inhibitor sorafenib improves treatment efficacy. A prior phase I study of the allosteric mTOR inhibitor temsirolimus combined with sorafenib demonstrated acceptable safety at the recommended phase II dose. Methods: We conducted a single-arm, multicenter phase II trial of the combination of temsirolimus 10 mg intravenously weekly plus sorafenib 200 mg b.i.d. The primary endpoint was time to progression (TTP) with efficacy target of median TTP of at least 6 months; secondary endpoints included overall survival (OS), objective response rate, safety, and alpha-fetoprotein (AFP) tumor marker response. Next-generation tumor sequencing was performed as an exploratory endpoint. Results: Twenty-nine patients were enrolled, including 48% with hepatitis C virus infection and 28% with hepatitis B virus; 86% had Barcelona clinic liver cancer stage C disease. Among 28 patients evaluable for efficacy, the median TTP was 3.7 (95% confidence interval [CI]: 2.2, 5.3) months, with 14% of patients achieving TTP of at least 6 months. The median OS was 8.8 (95% CI: 6.8, 14.8) months. There were no complete or partial responses; 75% of patients had stable disease as best response. AFP decline by at least 50% was associated with prolonged TTP and OS. Serious adverse events occurred in 21%; the most common treatment-related adverse events of CTCAE grade 3 or higher were hypophosphatemia (36%), thrombocytopenia (14%), and rash (11%). There were no grade 5 events attributed to sorafenib or temsirolimus. Tumor next-generation sequencing (NGS) was performed in a subgroup of 24 patients with adequate tumor samples. Tumor mTOR pathway mutations were identified in 42%. There was no association between tumor mutation profile and OS or TTP. Conclusions: The combination of temsirolimus and sorafenib demonstrated acceptable safety but did not achieve the target threshold for efficacy in this phase II study. Tumor NGS including the presence of mTOR pathway mutations was not associated with treatment response in an exploratory subgroup analysis.